STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMA SWASTA ESA PRAKARSA SELESAI TAHUN PELAJARAN 2024-2025 - Elia Rosdiana Manalu; Maulana Akbar Sanjani; Hamidah Darma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research seeks to provide a comprehensive description and analysis of the strategies employed by school principals in enhancing educational quality within the school setting. Utilizing a qualitative approach with a case study design, data were collected through observations, in-depth interviews, and document analysis conducted at a secondary school in Indonesia. The results indicate that the school principal holds a pivotal role in advancing education quality, which is carried out through several strategies, such as reinforcing visionary leadership, enhancing teacher competencies via training and academic supervision, fostering a positive school culture, and strengthening collaboration with parents and the wider community. Moreover, the principal incorporates information technology into both administrative functions and the teaching-learning process. The study concludes that the success of a principal’s strategy largely depends on managerial expertise, effective communication, and the collective support of all school stakeholders. These insights are intended to serve as a valuable reference for policymakers in developing strategic initiatives aimed at sustainable improvement in educational quality